Pengaruh Produk, Harga, Tempat, Promosi, Bukti Fisik, Orang, Proses terhadap Keputusan Pembelian Pada PT. Central Bearindo International Pekanbaru - SIlvia Sari Sitompul; mimi juwita (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
This study aims to determine the effect of the product, price, place, promotion, physical evidence, people, and processes on product purchasing decisions Bearing on a PT. Central Bearindo International. This study aims to determine the relationship between independent variables and the dependent variable. The total sample of 200 respondents who are consumers who buy Bearing on the PT. Central Bearindo International. Engineering samples using accidental sampling method. Data analysis method used is multiple linear regression. The results based on model test states that the marketing mix variables influence on purchase decisions Bearing on PT. Central Bearindo International. Partially stating that the variable product, price, physical evidence and processes influence on purchase decisions Bearing on PT. Central Bearindo International, while variable place, promotions, and no influence on purchase decisions Bearing on PT. Central Bearindo International. Of the seven variables studied, the variable product is the most influential variable on purchase decisions Bearing on PT. Central Bearindo International Keywords: Product, Price, Place, Promotion, Physical Evidence, People, Process, Purchasing Decision.